Genetic counseling in the Middle East: provider perspectives of patient attitudes and cultural challenges - Shruti Shenbagam; Alan Taylor; Ruchi Jain; Khalid Fakhro; Fowzan Alkuraya; Ahmad Abou Tayoun (Human Genomics)
Abstract Genomic advancements have led to increased utilization of genetic testing in clinical care, yet barriers to accessing genetic counseling and genomics services remain, particularly in the Middle East where inherited diseases are highly prevalent due to consanguinity. Limited knowledge of healthcare professionals’ experiences in genetic counseling in the Middle East necessitates understanding their perspectives for better service improvement in the region. As a pilot, a survey of 32 healthcare professionals providing genetic counseling services in the Middle East explored provider experiences, patient attitudes and cultural/psychosocial factors related to genetic testing. Among the participants, 21 providers (65.6%), caring for patients of multiple ethnicities, including Arabs, recognised that there are unique challenges to counseling between these patient groups. Thematic data analysis identified that higher levels of consanguinity and stoic nature of the people are unique cultural considerations in the region. Language barriers and limited resources were identified as genetic counseling challenges. Overall, patients demonstrated good coping abilities with a genetic diagnosis. Eighteen responses (56%) highlighted an overall positive attitude, with increasing awareness and acceptance towards genetic testing. This study highlights the need for further research and interventions to address the unique challenges and improve genetic counseling services in the Middle East.